A high-energy all-solid-state lithium metal battery with "single-crystal" lithium-rich layered oxides. Issue 5 (19th December 2022) - Yin, Xin; Li, Deyang; Hao, Liangwei; Wang, Yinzhong; Wang, Yongtao; Guo, Xianwei; Zhao, Shu; Wang, Boya; Wu, Lingqiao; Yu, Haijun
Abstract : The "single-crystal" lithium-rich layered oxide (SC-LLO) material is firstly used to construct the composite cathode for garnet-based all-solid-state batteries, which exhibit the high discharge capacity of ∼226 mA h g −1 and good capacity retention. Abstract : The "single-crystal" lithium-rich layered oxide (SC-LLO) material is applied for the first time to construct a composite cathode by a co-sintering process for garnet-based high-energy all-solid-state lithium metal batteries, which exhibit the high initial discharge capacity of ∼226 mA h g −1, and good capacity retention after tens of cycles.